Similarities and Differences between ICME-driven Shocks Observed by VEX (∼0.72 au) and WIND (∼1.0 au) - Mengsi Ruan; Pingbing Zuo; Zilu Zhou; Jiayun Wei; Xueshang Feng; Yi Wang; Qi Xu; Xiaojun Xu; Zhengyang Zou; Zhenning Shen (The Astrophysical Journal)
The features of interplanetary shocks driven by interplanetary coronal mass ejections (ICMEs) observed by WIND (∼1.0 au) and Venus Express (VEX; ∼0.72 au) during the same period are statistically analyzed by comparing their similarities and differences. It is found that the proportion of ICME-driven shocks in all shocks decreases slightly from ∼0.72 to ∼1 au. The yearly occurrence of ICME-driven shocks at both ∼0.72 and ∼1 au roughly follows the sunspot cycle, while the magnetic field ratio does not show such a correspondence. In each year, the annual medians of the shock angle for ICME-driven shocks at ∼1 au are consistently larger than those at ∼0.72 au, and the annual medians of the magnetic field ratio for events at ∼1 au are slightly smaller than those at ∼0.72 au. Planar magnetic structures (PMSs) downstream of ICME-driven shocks are also analyzed. Approximately 28.57% of the detected PMS events from VEX observations and 28.84% from WIND observations cover the entire 2 hr intervals downstream of the shocks, which are referred to as full PMS events. Through comparative analysis for VEX and WIND observations, it is found that strong and quasi-perpendicular ICME-driven shocks are the most preferable conditions for full PMS formation.